PENINGKATAN BAHASA EKSPRESIF MELALUI ONE DAY ONE BOOK DI KB AL MUHAJIRIN - Yuliana, Susi; Firdausi Nuzula Apriliyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the One Day One Book Program, identify the challenges encountered during its implementation, and analyze the improvement of expressive language skills among children aged 3–4 years at KB Al Muhajirin Puri Indah Tuban. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consisted of two cycles involving the stages of planning, action, observation, and reflection. The participants were 26 children aged 3–4 years. Data were collected through observation and documentation and analyzed using descriptive quantitative and qualitative techniques. The findings showed that the implementation of the One Day One Book Program gradually improved the children's expressive language skills. Classical learning mastery increased from 19.23% in the initial condition to 53.85% in Cycle I and reached 96.15% in Cycle II, exceeding the predetermined success indicator. The improvement was reflected in the children's ability to answer questions, express opinions, use new vocabulary, express their feelings, and retell stories. Initial challenges, including low self-confidence, limited vocabulary, and the use of less engaging learning media, were addressed through age-appropriate storybooks, varied instructional media, and positive reinforcement provided by the teacher. Based on the findings, it can be concluded that the One Day One Book Program is an effective learning strategy for improving young children's expressive language skills while promoting an active, enjoyable, and meaningful learning environment.